Neonatal outcome in randomized controlled trial of low dose oral misoprostol in comparison with intracervical Dinoprostone gel for labour induction - D. R., Savithri; R., Suvarna; Chennupalli, Prashanthi; S., Akshatha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Induction of labour is a therapeutic option when the benefits of delivery outweigh risks of continuing pregnancy. There are several agents for induction of labour to achieve better outcome of labour. Acceptable methods for induction are oxytocin infusion, dinoprostone gel, misoprostol and mechanical cervical dilators. Prostaglandins are the preferred choice in unripened cervix. To study the neonatal outcome in induction of labour with low dose oral misoprostol compared with intracervical dinoprostone gel and also to assess occurrence of meconium staining liquor. Methods: One hundred women with single live fetus, term gestation, cephalic presentation, reactive fetal heart pattern and Bishops score <6 were included in the study. They were randomized to receive either 6 doses of 25ug oral misoprostol every 3rd hourly or 0.5ug intracervical dinoprostone every 6th hourly for a maximum of 3 doses. Oxytocin was administered. Fetal outcome was assessed in terms of APGAR score, meconium staining and need for NICU. Results: Meconium stained amniotic fluid was high in misoprostol group (16%) compared to dinoprostone group (8%). NICU admissions were seen in 7 neonates in both groups. Conclusions: Low dose oral misoprostol is a safe method of labour induction. APGAR and NICU admission rates were comparable in both groups. Meconium staining was more in misoprostol group compared to dinoprostone group.